Sweated Industries and Sweated Labor: The London Clothing Trades, 1860-1914 - Tulchinsky, Gerald (Labour / Le Travail, 1986)
This article reviews the book, "Sweated Industries and Sweated Labor: The London Clothing Trades, 1860-1914," by James A. Schmiechen.
Keywords: Clothing industry; Nonfiction; REVIEWS; SCHMIECHEN; James A.; SWEATED Industries & Sweated Labor: The London Clothing Trades 1860-1914 (Book); books